CoTaZr/Pd multilayer with perpendicular magnetic anisotropy - COEY, JOHN (AIP Publishing, 2013)
We report a novel perpendicularly magnetized thin film [Co91.5 Ta 4.5Zr4/Pd]5 multilayer, which exhibits strong perpendicular magnetic anisotropy when grown on 5 nm of Pd and Ru seed layers. The Pd-seeded multilayer annealed at 300 °C shows an effective uniaxial anisotropy constant, K eff = 1.1 MJ m−3, with an anisotropy field as high as 1.6 T. The perpendicular anisotropy is sustained on annealing at 400 °C for 1 h. X-ray diffraction on multilayers with 30 repeats suggests that the use of amorphous CoTaZr reduces the stress of the stack, compared to [Co/Pd] multilayer.
PUBLISHED
Keywords: X-ray diffraction; Coercive force; Magnetic anisotropy; Annealing; Multilayers